EROSION HAZARD MAPPING IN SLEMAN REGENCY BASED ON RUSLE AND REMOTE SENSING - Rochmad Bayu Purnomoaji; Surya Murdani; Hamzah Saifuddin; M. Fadel Pahleva Yacoeb (Pangripta Sembada : Jurnal Perencanaan Pembangunan, 2026)
Soil erosion is a land degradation issue with implications for regional carrying capacity, hydrological risk, land productivity, and the effectiveness of local development. This study aims to map erosion hazards in Sleman Regency and formulate their implications for development planning. A spatial-quantitative approach was applied using the Revised Universal Soil Loss Equation (RUSLE) integrated with Geographic Information Systems and remote sensing. Data were collected from ten-year CHIRPS rainfall records, DEMNAS topographic data, soil-type maps, Sentinel-2 NDVI, and the 2024 land-use map of Sleman Regency. The analysis produced R, K, LS, C, and P factor maps, followed by erosion estimation using A = R x K x LS x C x P. Data accuracy and consistency were assessed through coordinate harmonization, raster resolution standardization, value-range validation, spatial inspection, and area-tabulation checks. The results show that the analyzed area covers 56,862.54 ha and is dominated by the very low erosion class, covering 22,766.04 ha (40.04%). However, moderate, high, and very high erosion classes cumulatively reach 27,524.70 ha (48.40%), with major concentrations on the northern slopes of Merapi and the Prambanan hills. These findings indicate that erosion hazard maps should be used as a basis for land-use control, land rehabilitation, drainage planning, and mainstreaming soil-water conservation in Sleman Regency development planning.